Methodological Considerations for Cost of Illness Studies of Enteric Fever. (29th July 2020) - Mejia, Nelly; Ramani, Enusa; Pallas, Sarah W; Song, Dayoung; Abimbola, Taiwo; Mogasale, Vittal
Abstract: This article presents a selection of practical issues, questions, and tradeoffs in methodological choices to consider when conducting a cost of illness (COI) study on enteric fever in low- to lower-middle-income countries. The experiences presented are based on 2 large-scale COI studies embedded within the Surveillance for Enteric Fever in Asia Project II (SEAP II), in Bangladesh, Nepal, and Pakistan; and the Severe Typhoid Fever Surveillance in Africa (SETA) Program in Burkina Faso, Ethiopia, Ghana, and Madagascar. Issues presented include study design choices such as controlling for background patient morbidity and healthcare costs, time points for follow-up, data collection methods for sensitive income and spending information, estimating enteric fever–specific health facility cost information, and analytic approaches in combining patient and health facility costs. The article highlights the potential tradeoffs in time, budget, and precision of results to assist those commissioning, conducting, and interpreting enteric fever COI studies.